Paideia and Performance Selected Essays from the 7th Interdisciplinary Symposium on the Hellenic Heritage of Sicily and Southern Italy - Reid, Heather L. (Parnassos Press - Fonte Aretusa, 2023)
Paideia is a word that signifies education or culture-two concepts that are only apparently distinct in Ancient Greek thinking. The performance of poetry, philosophy, rhetoric, drama, dance, and even athletics functioned simultaneously as education and culture. They entertained and unified communities by affirming shared heritage and interrogating common values. This process had special importance in Sicily and Southern Italy, where Hellenism was often a matter of education rather than ancestry. This volume explores the intersection of education and cultural performance in a variety of disciplines and from a variety of perspectives. Authors discussed include Sappho, Empedocles, Gorgias, Plato, and Aristotle. Contexts range from choral dance, to epideictic oratory, theatrical performance, philosophical dialogue, and gymnastic exercise. Taken together, these diverse essays reveal a cultural paideia aimed at realizing an ideal of human potential-not least by questioning human reality.